Enzymeless Hydrogen Peroxide Sensor Based on Mn-containing Conducting Metallopolymer - Martin, Cibely S. [UNESP]; Teixeira, Marcos F. S. [UNESP] (Elsevier B.V., 2012)
The [(Mn4O5)-O-IV(terpy)(4)(H2O)(2)](6+) complex, show great potential for electrode modification by electropolymerization using cyclic voltammetry. The voltammetric behavior both in and after electropolymerization process were also discussed, where the best condition of electropolymerization was observed for low scan rate and 50 potential cycles. A study in glass electrode for better characterization of polymer was also performed. Electrocatalytic process by metal centers of the conducting polymer in H2O2 presence with an increase of anodic current at 0.85 V vs. SCE can be observed. The sensor showed great response from 9.9 x 10(-5) to 6.4 x 10(-4) mol L-1 concentration range with a detection limit of 8.8 x 10(-5) mol L-1, where the electrocatalytic mechanism was based on oxidation of H2O2 to H2O with consequently reduction of Mn-IV to Mn-III. After, the Mn-III ions are oxidized electrochemically to Mn-IV ions. (C) 2012 Elsevier Ltd .... Selection and/or peer-review under responsibility of the Symposium Cracoviense Sp. z.o.o.
Keywords: peroxide; electrochemical behavior; Mn-containing conducting metallpolymer; biomimicking; voltammetric sensor